PEREMPUAN DAN MEDIA IKLAN SUATU ANALISIS KETIDAKADILAN DALAM MEDIA SOSIAL - Ihsan, Muhammad Alim (Musawa: Journal for Gender Studies, 2017)
In the people’srealities, women’s problems and advertising is one thing that cannot be separated, because women in the eye of society become an important scourge in advertisements without women’s identity feels empty and will not create balance in life. The balance is that advertising is more likely to build a reality by exploiting norms or values and secondly no single theory is specifically used to examine gender issues. The theory developed for gender is adopted from the theories that move in the field related to gender issues. The theory in question is structural functional theory, conflict theory, feminism theory and others.